Unusual case report of an adenomatoid odontogenic tumor in the mandible: 3-years of follow-up - Andreis, Jéssica Daniela; Gross, Dayane Jaqueline; Fischborn, Amanda Regina; Mecca, Leomar Emanuel Almeida; Rosa Chioca, Lea; Zanelato, Cristina Maria de Freitas; Claudino, Marcela; Lúcio Fernandes, Tito; Franco, Gilson Cesar Nobre (ARCHIVES OF HEALTH INVESTIGATION, 2021)
This case report showed an AOT in a 12-year-old female patient referred for orthodontic-surgical of both impacted right mandibular canine and lateral incisor. Cone beam computed tomography revealed a well-defined mixed hyperdense/hypodense lesion, involving the crown of the mandibular lateral incisor. The surgery consisted in surgical exposure of the mandibular right canine and lateral incisor, bonding of the lateral incisor for orthodontic traction and curettage of the mandibular lesion. Histopathological examination revealed several columnar epithelial cells with minimal stromal connective tissue, lobular pattern and rosettes and duct-like structures, confirming the diagnosis of AOT. After, the patient was referred for orthodontic traction of the impacted teeth. At 1 and 3-year postoperatively, follow-ups examinations showed extensive bone repair, resolution of the tooth-retention and absence of recurrence. Although AOT is an uncommon lesion in the mandible, it should be considered in the differential diagnosis of the mixed profile lesions in this region.